Systematic review with meta‐analysis: impact of baseline resistance‐associated substitutions on the efficacy of glecaprevir/pibrentasvir among chronic hepatitis C patients. Issue 5 (14th January 2020) - Singh, Achintya D.; Maitra, Souvik; Singh, Nita; Tyagi, Payal; Ashraf, Anzar; Kumar, Ramesh; Shalimar,
Summary: Background: The effect of baseline resistance‐associated substitutions (RAS) on the sustained virologic response at 12 weeks (SVR12) among chronic hepatitis C (CHC) patients receiving the second generation, pan‐genotypic glecaprevir/pibrentasvir (G/P) regimen is unclear. Aim: To assess the effect of RAS on the SVR12 in CHC patients treated with G/P regimen. Methods: The EMBASE, MEDLINE and Cochrane central register of controlled trials databases were searched for relevant studies published before 1 March 2019. The principal outcome was to compare the SVR12 in CHC patients with and without baseline RAS, particularly in genotype‐1, genotype‐3 and direct‐acting anti‐virals (DAAs) failure patients. The outcomes were pooled using a random‐effects model and odds ratio (OR) was calculated. The risk of bias was assessed using the Cochrane risk of bias tools for randomised and nonrandomised interventional studies. Results: After initially identifying 410 studies, 3302 patients from 17 studies were included. Among 50 cases of virologic failures, 48% had genotype‐3 infection, 44% genotype‐1 infection and 36% DAA‐failure patients. Baseline RAS were present in 44(88%) patients. The most common NS5a and NS3 mutations were Y93H and A166S respectively. The odds of SVR12 were significantly reduced in patients with any baseline RAS (NS3 and/or NS5a) (OR 0.32, 95%C I[0.15, 0.65], I 2  = 0%) and NS5a substitutions (OR 0.36, 95%CI [0.18, 0.73]). The impact of RAS on SVR12 was significant among genotype‐3 patients, but not among genotype‐1 or DAA‐failure cases. The presence of Y93H and A30K mutations significantly impacted SVR12 rates in genotype‐3 patients. Conclusion: Baseline NS3 or NS5a RAS, especially the NS5a substitutions—A30K, Y93H, decrease the odds of achieving SVR12 in genotype‐3 CHC patients. Abstract : LINKED CONTENT This article is linked to Kwong and Kwo and Singh et al papers. To view these articles, visit https://doi.org/10.1111/apt.15656 and https://doi.org/10.1111/apt.15666 .